UNDERSTANDING THE RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND CONFLICT MANAGEMENT: A CASE OF UNIVERSITY LIBRARY MANAGERS IN PAKISTAN - Sajjad Ahmad Shehzad Ahmad , Muhammad Ibrahim; Safir Ahmad Khan (IJoLIS, 2025)
The study examined the Emotional Intelligence (AI) level, Conflict Management (CM) styles, and their relationship among university library managers in Pakistan. Emotional intelligence was found to be strongly associated with conflict resolution strategies in libraries, contributing to the success of emotionally intelligent library managers in their professional activities. Previous research has also supported the importance of regular communication and interactions between staff and clients for achieving success in library management (Ramsey, 2004). Data for the study was collected through a questionnaire that included two prominent scales: the ESCI scale to measure the respondents' emotional intelligence level and the ROCI-II scale to assess conflict management styles. The study population consisted of 560 library managers in public and private university libraries, as reported in Ahmad, Amen, and Ullah (2021). However, the sample was limited to 149 university library managers working in libraries in Khyber Pakhtunkhwa and Islamabad. A total of 149 questionnaires were distributed digitally and physically to the respondents, with 101 questionnaires returned. The results indicated that library managers exhibited high EI, with favorable scores in different dimensions of EI. No significant gender-based differences were observed in the use of Emotional Intelligence or its dimensions among university library managers. The study also revealed that the most frequently used Conflict Management styles among library managers were obliging and dominating, while the compromising style was the least utilized. The Pearson correlation test was employed to assess the relationship between emotional intelligence and conflict management styles among library managers showing a significant and strong association between emotional intelligence and conflict management styles among university library managers in Pakistan. In Pakistan, this study was the pioneering research to examine the connection between emotional intelligence and conflict management styles. The study's findings suggest the implementation of training workshops and intervention programs aimed at improving the emotional intelligence and conflict management skills of library managers. Additionally, organizations are encouraged to allocate their time and resources to gain a deeper understanding of effective conflict management techniques, which can lead to enhanced performance.